A Serial Mediation Model of the Brain Drain Perceptions Among Health and Tourism Students - Sebahat Gözüm; Gülseren Yurcu; Ayşegül Ilgaz; Dilek Hale Aybar (AVES, 2024)
AIM: It was aimed to explore the serial mediation role of self-efficacy and financial anxiety levels in the impact of health and tourism students' life satisfaction on brain drain perceptions. METHODS: In this descriptive study, the data from 403 participants were collected using four scales (Brain Drain Attitude, Life Satisfaction, SelfEfficacy, Financial Anxiety) between May and July 2022 in Antalya, Türkiye and serial mediation model and regression analysis were conducted. RESULTS: From the data, 83.3% tourism, 74.8% nursing, 56.5% dentistry, and 55.7% medical school students indicated they were contemplating migrating following graduation. Life satisfaction had a positive effect on self-efficacy and a negative effect on financial anxiety, and self-efficacy on financial anxiety had a positive effect. Life satisfaction had a direct negative effect on brain drain, while self-efficacy and financial anxiety had positive effects on brain drain. Students' perceptions of life satisfaction were important antecedent of brain drain intention, and self-efficacy perception and financial anxiety have mediating effects in this effect. The factors most influencing their intent to migrate were brain drain attitude and faculties. Financial anxiety, self-efficacy, and intention to go abroad were variables affecting the perceptions of brain drain. CONCLUSION: The migration intentions and brain drain attitudes expressed in this study predict an immediate and severe threat to the sustainability of the country's healthcare and tourism service. Interventions such as improving financial anxiety and providing life satisfaction are required.